A new species of genus Parhyale Stebbing, 1897 (Crustacea, Amphipoda, Hyalidae) from Gujarat State, India - Myers, Alan A.; Trivedi, Jigneshkumar N.; Gosavi, Swapnil; Vachhrajani, Kauresh D. (Zootaxa, 2017)
A new species of amphipod, Parhyale piloi sp. nov., is described from India. The taxon is fully described and figured and is compared with known species with which it could be confused.